CHALLENGES EXPERIENCED IN DRUG AND SUBSTANCE ABUSE CESSATION EFFORTS AMONG STUDENTS IN SECONDARY SCHOOLS: A CASE OF MACHAKOS MUNICIPALITY, MACHAKOS COUNTY, KENYA - Makau, Beth James; Kaaria, Dr Zipporah; Katiba, Doreen (International Journal of Psychology, 2019)
Purpose: The purpose of this study was to investigate into the challenges experienced in drug and substance abuse cessation efforts by students in secondary schools in Machakos County. The study used the study objectives; to investigate individual challenges experienced by students in secondary schools in Machakos Municipality in their effort to stop abusing drugs and to establish school challenges experienced by students in secondary schools in Machakos Municipality in their efforts to stop abusing drugs. Methodology: The study used descriptive design. From the 27 schools within the municipality, 9 were purposively sampled. Each school provided a total of 12 respondents, 3 students from each form. One deputy principal, and one Guidance and counseling teacher from each school formed the total of 136 respondents. Questionnaires were administered to both students and teachers. Focus group discussions were conducted among students and interviews were done with kiosk owners around the school compounds. The various methods of data collection ensured triangulation and richer data. Data analysis was carried out using the Statistical Package for Social Sciences (SPSS) utilizing descriptive rocedures. The results were presented in frequency distribution, tables, and percentages. Findings: The findings revealed that 46.7% of both and girls in public and private secondary schools were aware that students abuse drugs. Majority 66.7% indicated that withdrawal syndromes were the individual challenges faced in the cessation efforts. .45.3% indicated that peer pressure was the major school challenge experienced in cessation efforts. Unique Contribution to Theory, Practice and Policy: Recommendations included having trained drug and abuse counselors in schools to be able to help the students who are involved in the substances of abuse, teachers, counselors, and the ministry of education, parents, and the general public may benefit from these findings a lot. Although drug and substance abuse cuts across all genders, there is hope for the quitters.